The revenge of the Demon Headmaster - Cross, Gillian (Oxford : Oxford University Press, 2017)
Everyone is talking about the latest TV show, Hunky Parker. It's the latest craze and soon everyone in school is completely hooked on it. Ingrid tries to convince her friends to watch, but they're just not interested. At last she manages to persuade them and once they start watching it, something very weird happens . . . and it could involve the Demon Headmaster! Great fun and just a little bit frightening, Gillian Cross's beloved characters still holds readers under his hypnotic spell. Exciting and page-turning adventures. The Demon Headmaster series is impossible to resist.
Originally published: as Hunky Parker is watching you. 1994.
Keywords: Demon Headmaster -- (Fictitious character) -- Juvenile fiction; Children's stories